2021
DOI: 10.1002/alz.12433
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Alzheimer's disease drug trials: The importance of eligibility criteria

Abstract: Introduction:To generalize safety and efficacy findings, it is essential that diverse populations are well represented in Alzheimer's disease (AD) drug trials. In this review, we aimed to investigate participant diversity in disease-modifying AD trials over time, and the frequencies of participant eligibility criteria.Methods: A systematic review was performed using Medline, Embase, the Cochrane Library, and Clinicaltrials.gov, identifying 2247 records. Results:In the 101 included AD trials, participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 70 publications
7
76
0
Order By: Relevance
“…Despite these milestones, we observed no improvements over time in the racial or ethnic diversity of these trial populations. This result is consistent with a previous systematic review of 101 AD trials of candidate disease-modifying therapies, which showed no improvement (or worsening) in enrollment of participants from minoritized racial and ethnic groups over time between 2001 to 2019 [ 39 ]. Nearly 25% of older Americans are from a racial or ethnic minority group [ 40 ] and certain groups may be overburdened by AD [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Despite these milestones, we observed no improvements over time in the racial or ethnic diversity of these trial populations. This result is consistent with a previous systematic review of 101 AD trials of candidate disease-modifying therapies, which showed no improvement (or worsening) in enrollment of participants from minoritized racial and ethnic groups over time between 2001 to 2019 [ 39 ]. Nearly 25% of older Americans are from a racial or ethnic minority group [ 40 ] and certain groups may be overburdened by AD [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding suggests that overall interest in dementia prevention research participation may be consistent across different sexes, racial and ethnic backgrounds, and socioeconomic statuses. On the other hand, structural and logistical components of AD prevention clinical trials, such as recruitment methods, eligibility criteria, and access to trial sites, pose significant barriers to participation and disproportionately impact communities of color ( 13 ). Previous research on recruitment of under-represented groups to AD clinical trials suggests community outreach may be the most effective tool to address these disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate and slow recruitment of volunteer participants to dementia prevention clinical trials, however, is delaying progress and requires urgent intervention ( 4 – 9 ). Critically, under-representation of racial and ethnic groups in prevention trials limits the generalizability of results to sub-populations at greatest risk for AD ( 6 , 10 13 ). Black and Hispanic adults are at 2 and 1.5 times greater risk to develop AD compared to their Non-Hispanic White counterparts, respectively, but make up just 10% of AD research participants ( 10 , 11 ) compared to 32% of the general population ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the exact cause of AD has not been elucidated, studies have found that AD is the result of a combination of genes, lifestyle, and environmental factors, caused in part by specific genetic changes [ 6 9 ]. A combination of drug therapy, non-drug therapy, and careful nursing can reduce symptoms and delay the progression of the disease [ 10 12 ], but there is no specific drug that can cure AD or effectively reverse the progression of the disease. The course of Alzheimer's disease is about 5–10 years, and a few patients can survive for more than 10 years.…”
Section: Introductionmentioning
confidence: 99%